Preoperative p53, bcl-2, CD44 and E-cadherin immunohistochemistry as predictors of biochemical relapse after radical prostatectomy. - Brewster, S; Oxley, J; Trivella, M; Abbott, C; Gillatt, D (Elsevier, 1999)
Purpose Since radical prostatectomy is performed to cure prostate cancer, identification of markers enabling preoperative prediction of relapse after radical prostatectomy is essential to counsel and select patients for adjuvant therapy. Aberrant p53, bcl-2, CD44 and E-cadherin immunohistochemistry has been associated with aggressiveness in prostate cancer. We assessed these biomarkers in biopsy and radical prostatectomy specimens as predictors of biochemical relapse. Materials and Methods A total of 76 patients with untreated clinically localized prostatic adenocarcinoma underwent radical prostatectomy. Preoperative (prostate specific antigen, biopsy Gleason score) and postoperative (pathological stage and margin status) variables, biopsy and radical prostatectomy biomarker immunohistochemistry were correlated with relapse. Univariate and multivariate statistical analyses identified significant predictors. Results Of the 76 patients 23 (30%) had relapse (mean followup 38 months). Aberrant p53, bcl-2, CD44 and E-cadherin expression was observed in 64,12,85 and 12% of biopsies and 57,20, 64 and 49% of radical prostatectomy specimens, respectively. Biopsy Gleason 7 to 10 and biopsy p53, respectively, gave the highest positive and negative predictive values for relapse. Relapse occurred in 13% of patients with normal biopsy p53 and in half with aberrant p53. Multivariate analysis revealed Gleason score and p53 to be independent preoperative predictors (p = 0.01 and 0.02, respectively). Estimated risk of relapse was 3.5 times higher in patients with Gleason scores 7 to 10 and 24% higher in those with aberrant p53. Significant postoperative predictors were bcl-2, p53, Gleason score and margin status (p = 0.01, 0.01, 0.04 and 0.01, respectively). Conclusions Aberrant biopsy p53 is associated with a significantly worse outcome after radical prostatectomy than normal p53, highlighting a potential clinical role for p53. Postoperative p53 and bcl-2 were significant predictors of outcome after radical prostatectomy.